Emerging Asia: essays on crises, capital flows, FDI and exchange rates - Rajan, Ramkishen S. (New York, 2011)
This book on the different aspects of international economic policy covers financial crises, reserve accumulation, capital flows and currency wars as well as issues relating to foreign direct investment and developments in China and India.
Keywords: Capital flows